Topical issues of myocardial infarction incidence statistics - E. P. Kakorina; I. V. Samorodskaya; S. Yu. Martsevich (Российский кардиологический журнал)
The article presents the features of statistical assessment of myocardial infarction (MI) incidence and prevalence in Russia and some countries of the world. The existing methodology for assessing incidence in Russia does not take into account all cases of MI. Local registries (based on one or several institutions with limitations on age and clinical features) are not a sufficient basis for assessing incidence or prevalence, since they do not represent a representative sample of the population in terms of demographic characteristics. There is a high probability of incorrect use of I22 codes. There are no uniform accounting rules in the world (ICD codes for MI accounting are not similar to universal definition of MI).